Electrical properties of copper- and silver-containing superionic (Cu1−xAgx)7SiS5I mixed crystals with argyrodite structure - Studenyak Ihor; Студеняк Ігор; Pogodin Artem; Погодін Артем; Viktor Studenyak; Студеняк Віктор; Izai Vitalii; Ізай Віталій; Filep Mykhailo; Філеп Михайло; Filep Mihály; Oleksandr Kokhan; et al. (Elsevier, 2020)
Abstract. The copper and silver containing (Cu1−xAgx)7SiS5I mixed crystals with argyrodite structure have been grown by direct solidification using the Bridgman-Stockbarger technique. Measurements of electrical conductivity of mixed crystals by means of impedance spectroscopy were carried out in the frequency range from 2 × 101 Hz to 2 × 106 Hz and temperature range 292–378 K. Frequency dependences of total electrical conductivity were studied, Nyquist plots were constructed and analysed. The influence of Cu+ → Ag+ cation substitution on the total electrical conductivity, on the electronic and ionic components of the electrical conductivity as well as on their activation energies for (Cu1−xAgx)7SiS5I mixed crystals was investigated.
Contents: https://www.sciencedirect.com/journal/solid-state-ionics/vol/345/suppl/C Editorial board: https://www.sciencedirect.com/journal/solid-state-ionics/about/editorial-board
Keywords: Argyrodites; Crystal growth; Nyquist plot; Electrical conductivity; Activation energy; Compositional dependence